Electronic commerce technologies and changing product distribution. (1st January 1998) - Rhodes, Ed; Carter, Ruth
The paper draws on research into retail supply systems. It illustrates a spectrum of retailing strategies adopted by large companies and SM Es in Europe and the USA. It considers the evolving strategies of companies of different types and at different locations in consumer product supply systems. It links these strategies to fundamental shifts in market conditions, and to the impacts of: intensified rivalries between established players; companies invading new territories; and growing competition from new entrants. In large part, these impacts are related to progressive experimentation with, and application of, electronic commerce technologies. They relate both to changes in upstream supply systems, and to use of electronic media such as the Internet and interactive television systems to disseminate product information and to sell products. it is argued that the long-term trend appears to be towards a more "mixed economy" than is often predicted. The nature of this mix will depend on the abilities of manufacturers and smaller retailers to respond to the growing power of the emerging global retail chains.